Essentials of Sarbanes-Oxley - Anand, Sanjay (Hoboken, N.J. : John Wiley & Sons, 2007)
The book gives the 'big picture ' of the Sarbanes - Oxley Act, putting together various pieces - finance, accounting, audit, legal, IT, ethics and also having references to the new changes in auditing standards while emphasizing achieving sustainable compliance - practical and realistic approaches.
Includes index.
rua 28/11/13
Loans
Keywords: Corporations; Disclosure of information; Financial statements; Directors of corporations; Corporate governance; Law and legislation; United States